2007
DOI: 10.1021/ac061578f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Stability, and Cellular Internalization of Gold Nanoparticles Containing Mixed Peptide−Poly(ethylene glycol) Monolayers

Abstract: Gold nanoparticles have shown great promise as therapeutics, therapeutic delivery vectors, and intracellular imaging agents. For many biomedical applications, selective cell and nuclear targeting are desirable, and these remain a significant practical challenge in the use of nanoparticles in vivo. This challenge is being addressed by the incorporation of cell-targeting peptides or antibodies onto the nanoparticle surface, modifications that frequently compromise nanoparticle stability in high ionic strength bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
320
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(343 citation statements)
references
References 22 publications
20
320
1
2
Order By: Relevance
“…But the molecular weight of these PEGs is usually larger than 1000 Da. 41,42 In this study, the molar mass of PEG units was low (M = 281) and the interactions between water and PEG chains were weak, so the stability of Au@PEG-F NPs was sensitive to solution pH. The sensitivity of the assay to PFCs at different solution pHs was studied with the concentrations of PFOS ranging in 1−1000 μg L −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…But the molecular weight of these PEGs is usually larger than 1000 Da. 41,42 In this study, the molar mass of PEG units was low (M = 281) and the interactions between water and PEG chains were weak, so the stability of Au@PEG-F NPs was sensitive to solution pH. The sensitivity of the assay to PFCs at different solution pHs was studied with the concentrations of PFOS ranging in 1−1000 μg L −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…in an increased half-life in the blood stream. PEG-modified nanoparticles are more stable at high salt concentrations and in biological environments; they show less non-specific binding to proteins and cells (Gref et al 2000;Ballou et al 2004;Liu et al 2007bLiu et al , 2008van Vlerken et al 2007;Daou et al 2009). …”
Section: (B) Poly(ethylene Glycol)mentioning
confidence: 99%
“…In addition, examples for particle synthesis (Slocik et al 2005) and phase transfer (Euliss et al 2003) with the help of peptides have been reported. Making use of the biological functionality of certain peptides, the specific uptake of nanoparticles by cells can be optimized by conjugation of nanoparticles with the corresponding peptide, as reported for Au nanoparticles Liu et al 2007b;Nativo et al 2008) or quantum dots (Pinaud et al 2004) by ligand exchange with cysteine-containing peptides, as well as the reaction of the immune system towards nanoparticles may be modulated by the peptide coating (Bastus et al 2009). Also, coating of quantum dots with lipids pre-modified with e.g.…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…For example, functionalization with nucleic acids or proteins may destabilize AuNPs, and to improve the colloidal stability the biospecific molecule is mixed with filler molecules providing both steric stabilization and biocompatibility. [12][13][14][15] Oligo(ethylene) glycols (OEGs) are commonly used for steric stabilization of particles, [16,17] including stabilization of liposomes used as drug delivery vehicles, where they also prevent the triggering of immune responses. [18] As an alternative, we have synthesized the oligosaccharides 1-3 ( Figure 1) which presumably are rod-like [19] Immobilization of thiol compounds on gold surfaces into self-assembled monolayers (SAMs) is widely used to prepare well-defined and versatile model surfaces for studies of protein adsorption and biofouling.…”
Section: Introductionmentioning
confidence: 99%